Evaluation of the Suitability of Spatial Structure in Tegal City, Central Java Province - Rambe, Syavitri Sukma Utami; Wahyuningtias, Loetvy; Cahyana, Alifan (Jurnal Ilmiah Telsinas, 2025)
As regulated in Law No. 26 of 2007 concerning Spatial Planning, the urban spatial structure is an arrangement of settlement centres and infrastructure networks that support socio-economic activities through hierarchical functional relationships. In Tegal City, one of the crucial infrastructure elements is the road network, especially the North Coast national route, commonly called the Pantura Route. The Pantura Route strategically affects urban mobility and connectivity between regions. Its location in the city centre makes this route an important arterial corridor connecting major cities on Java Island, such as the Jakarta-Tegal-Purwokerto-Yogyakarta-Surabaya route. However, the high intensity of land use for economic, social, and educational activities has caused various problems, such as traffic accidents. In 2018, 59% of accidents occurred along this route, although this route only covers 13% of the total length of roads in Tegal City. Other problems include limited road infrastructure, physical damage to roads, and low road accessibility, which are also supporting factors. Important local-scale activities along the Pantura route, such as schools, health centres, and trade activities, raise concerns regarding the suitability of spatial structures and safety, especially when compared to national Standards (SNI 03-1733-2004). The method used in this study uses primary and secondary surveys and qualitative descriptive analysis, namely content analysis. The results of this study indicate that the deviation of spatial structures that occur in Tegal City is more than 50% seen from the existence of educational facilities (elementary and junior high schools), health facilities (health centres), and markets with a local scale that are not appropriate along the Pantura route. With regional authority within the framework of Law No. 23 of 2014 concerning Regional Autonomy, the city government is expected to be more active in managing spatial planning, especially spatial structures, so that deviations do not occur. This study aims to evaluate the suitability of the spatial structure of Tegal City by evaluating the function of the road network and the scale of service facilities based on urban environmental planning Standards. The findings of this study are expected to support effective and sustainable spatial planning of Tegal City.